A entrada de sal num espaço insular: Ilha da Madeira (1750-1832) - Santos, Filipe dos (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The purpose of this paper is to study the input of salt, from 1750 to 1832, in an insular space: the island of Madeira. The perception of this supply trade will be based, primarily, in a documental source of the municipality of Funchal (where is the only port of Madeira with conection with the exterior): the books of Registo dos Navios entrados no Funchal e despachos da Casa da Saúde. Through a quantitative approach, the topics of analysis are: conjunctural movements of importation; position of Madeira as a scale for salt in the Atlantic; areas of origin; duration of trips; types of ships carriers of salt.